Procedure writing principles and practices - Wieringa, Douglas 1960- (Battelle Press, 1992)
A reference for the procedure writer, whether these are business procedures, procedures for ISO9000 compliance, plant procedures or safety procedures. It presents the principles that underlie effective procedures and explains these principles in simple terms.